Efek Ekstrak Etanol Kulit Batang Rhizophora apiculata terhadap Kadar Kolesterol Total Darah pada Rattus norvegicus Jantan yang Diinduksi Deksametason - Iswara, Karisma Kasih; Andisari, Hendrata Erry; Handajani, Fitri; Puspita, Angela (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2025)
Introduction: Hyperlipidemia is an increase in blood lipid levels above normal limits, potentially leading to atherosclerosis and cardiovascular disease. Rhizophora apiculata contains flavonoids that have the potential to lower total blood cholesterol levels. Research on the hypolipidemic effects of R. apiculata is still limited, particularly in dexamethasone-induced animal models. Therefore, this study provides a new contribution to the use of mangrove biota as natural antihyperlipidemic agents. Purpose: This study aims to determine the effect of administering Rhizophora apiculata extract on total blood cholesterol levels in dexamethasone-induced Rattus norvegicus. Methods: This experimental study used a post-test only control group design with 40 male rats divided into four groups: negative control (K–), positive control (K+; induced by dexamethasone at 5 mg/kg BW for 7 days), prophylaxis group (KP; given R. apiculata extract at 56 mg/kg BW from day 8 until the end and induced by dexamethasone like K+), and therapy group (KT; given the extract simultaneously with dexamethasone induction). After treatment, total cholesterol levels were measured from intracardially drawn blood. Results: One-way ANOVA analysis showed a significant difference between groups (p < 0.001). However, post-hoc tests showed no significant difference between the positive control group and the prophylaxis (p = 0.435) or therapy (p = 0.397) groups. Conclusion: Although administration of Rhizophora apiculata extract as prophylaxis or therapy did not significantly reduce total cholesterol levels in dexamethasone-induced Rattus norvegicus, these findings suggest that further research is necessary to elucidate the mechanisms and potential efficacy of R. apiculata active compounds as natural antihyperlipidemic agents. Future studies should consider exploring different dosages, modes of administration, or alternative experimental models to better determine the therapeutic potential of this mangrove extract.